World Economic and Social Survey 2003 - United Nations (United Nations, 2006)
The World Economic and Social Survey is the United Nations annual analysis of current developments in the world economy and emerging policy issues. It contains forecast of short-term global and regional economic trends and reviews major developments in international trade. Part One of this year’s Survey revolves around the economic recovery that is underway in some developed market economies and some developing countries. Part Two explores current social issues that are interlinked with economic development. Special attention is given to public-private cooperation in the light of drastic transformation of the role of the government. The Survey includes statistical tables, which give standardized data on international trade and finance, incorporating current data and forecasts. It is essential for decision makers in government and business, and provides valuable information to all interested in the trends of global economy.